Can Circular Economy Strategies Limit the Prospective Dysprosium Demand in the European Union? - Eheliyagoda, Disna; Veluri, Badrinath; Liu, Gang; Ramanujan, Devarajan (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Dysprosium (Dy) is a high critical rare earth element, which is basically used for improving the thermo-magnetic properties in various low carbon products. This research provides a detailed examination on the evolution of Dy demand, in-use stock, and end-of-life (EoL) under ambitious climate targets and demand shrinkages that can be expected due to the implementation of two circular economy strategies: material efficiency and end-of-life recycling in 13 product sectors in the European Union from 2022 to 2050. Our results indicate that future Dy demand, in-use stock accumulation, and EoL generation are likely to be exacerbated by High-APS (Announced Pledges Scenario) and High-NZE (Net Zero Emissions by 2050 Scenario). Moreover, the circular economy strategies used in this study will contribute to significant decreases in the future Dy demand when such strategies are combined and applied in a high magnitude under High-APS and High-NZE scenarios. Recent efforts in the partial and full elimination of Dy mainly in high-tech products such as wind turbines and electrical vehicles are admirable, however, it is necessary to more focus on improving the implementation of circular economy strategies in manufacturing processes to mitigate future Dy supply uncertainties in the European Union.